Evaluating the Implementation of English Language Teaching in Higher Education Based on Students’ Perceptions - Husain, Nurlaila (Jurnal Riksa Cendikia Nusantara, 2025)
This study aims to evaluate the implementation of English language teaching in higher education based on students’ perceptions by integrating instructional interactivity, clarity of instruction, feedback quality, and learning barriers within a unified analytical framework. A descriptive quantitative approach was employed, involving 40 fifth-semester students in the 2025–2026 academic year. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, including mean scores, standard deviations, and agreement percentages. The findings indicate that students generally perceive the instructional structure and feedback practices positively, reflecting the application of constructive alignment principles, Communicative Language Teaching (CLT), and formative assessment. However, the consistency of interactive teaching practices and transparency in assessment still require further strengthening. Infrastructure limitations and restricted access to learning technology emerged as the primary barriers. These findings suggest that improving the quality of English language teaching requires a holistic approach that integrates sound instructional design, reflective assessment practices, and adequate institutional support systems.